Predictive Measures in Child Language Development: The Role of Familial History and Early Expressive Vocabulary. - Capelli, Elena; Dondena, Chiara; Luisa Lorusso, Maria; Mascheretti, Sara; Pozzoli, Raffaella; Salandi, Antonio; Molteni, Massimo; Riva, Valentina; Cantiani, Chiara (Journal of Speech, Language & Hearing Research, 2024)
3 years of age is challenging. Among early risk factors, research has focused on having a positive familial history (FH+) for language or literacy problems and on late language emergence, that is, late-talker (LT) status. The interaction between these two risk factors and their cumulative effect is still debated. Here, we (a) investigate the effect of FH+ on 24-month language development, (b) test for cumulative effects of FH+ status and early language delay on 36-month language outcomes, and (c) disentangle the direct and indirect effects of familial history (FH) on the language outcome. Method: One hundred eighty-five Italian children were followed up longitudinally between 24 and 36 months of age (64 FH+ and 121 FH-) through parental questionnaires and direct child assessment. Results: At the age of 24 months, the FH+ group showed worse expressive vocabulary and higher prevalence of LT. At the age of 36 months, main effects of LT and FH were identified on lexical and phonological performances, respectively. Interestingly, significant interaction effects were identified on expressive vocabulary and phonological processing. Path analysis highlights that FH had a direct effect on later measures of phonology, whereas its effect on 36-month lexical abilities was indirect, via measures of expressive vocabulary at 24 months. Conclusions: The study suggests specific predictive roles of FH and LT status on language development. Interestingly, FH+ seems to represent an additive risk for LT children. The use of cumulative risk measures is confirmed as a powerful approach to identify those children with the highest probability of developing persistent language difficulties.